2002
DOI: 10.1001/archopht.120.6.731
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Visual Acuity Associated With Cystoid Macular Edema in Neovascular Age-related Macular Degeneration

Abstract: To determine the prevalence and visual significance of cystoid macular edema (CME) in eyes with subfoveal neovascular age-related macular degeneration using optical coherence tomography (OCT). Materials and Methods:The medical records of 61 consecutive patients initially seen with nondisciform subfoveal neovascular age-related macular degeneration were retrospectively reviewed. All patients underwent fluorescein angiography and OCT imaging. Eyes with intraretinal hyporeflective spaces in the macula in the OCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 20 publications
(19 reference statements)
1
44
2
3
Order By: Relevance
“…No information was given on the visual acuity of the patients presenting with this fluorescein angiographic finding. In a recent study, 14 cystoid macular edema was demonstrated on optical coherence tomography imaging in 46% of 61 eyes with subfoveal choroidal neovascularization associated with age-related macular degeneration, more commonly in choroidal neovascularization containing classic component. The presence of cystoid macular edema and increased foveal thickness correlated with decreased visual acuity, as was noted in our study.…”
Section: Our Findings Show That Pdt Is Well Tolerated In Amentioning
confidence: 96%
See 1 more Smart Citation
“…No information was given on the visual acuity of the patients presenting with this fluorescein angiographic finding. In a recent study, 14 cystoid macular edema was demonstrated on optical coherence tomography imaging in 46% of 61 eyes with subfoveal choroidal neovascularization associated with age-related macular degeneration, more commonly in choroidal neovascularization containing classic component. The presence of cystoid macular edema and increased foveal thickness correlated with decreased visual acuity, as was noted in our study.…”
Section: Our Findings Show That Pdt Is Well Tolerated In Amentioning
confidence: 96%
“…The authors suggested that the retinal thickening (macular edema) may be a contributing factor to the decreased visual acuity in patients with age-related macular degeneration. 14 Cystoid macular edema has been described as one of the angiographic features of retinochoroidal anastomoses in the setting of neovascular age-related macular degeneration. In our series, 6 of the 12 eyes with cystoid macular edema that lost more than 3 lines of Snellen acuity also had retinochoroidal anastomoses on indocyanine green angiography.…”
Section: Our Findings Show That Pdt Is Well Tolerated In Amentioning
confidence: 99%
“…7 In other longitudinal studies, OCT parameters, such as maximum retinal thickness, foveal thickness, or cystoid changes, were associated with decreased distance VA at baseline and follow-up. 5,12 Vision outcomes resulting from the treatment of AMD-CNV have been evaluated primarily by using the ETDRS 0.1 logMAR chart. [8][9][10] However, visual acuity is recognized to have significant limitations in evaluating vision, especially in the eye with macular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid accumulation in the retina results in retina thickening with or without clear cysts, while subretinal or sub-RPE fluid is seen as clear spaces in these locations. A previous report [9] indicated that cystoid macular edema was a common finding in patients with CNV secondary to AMD. Moreover, the presence of macular edema and resulting foveal thickening was associated with worse visual acuity in those patients.…”
Section: Introductionmentioning
confidence: 99%